T. A Perry, Art and meaning in Berceo’s "Vida de Santa Oria". Yale University Press, New Haven & London, 1968; x + 231 p. (Yale Romanie’Studies, Second Series, 19). - Astey, Luis (Nueva Revista de Filología Hispánica (NRFH), 2007)
Se reseñó el libro: Art and meaning in Berceo's "Vida de Santa Oria".